A swell toughening strategy for elastomers having surface cracks. (January 2017) - Bacca, Mattia; Fleck, Norman A.; McMeeking, Robert M.
Abstract: The theoretical basis is developed for a strategy for enhancing the toughness of elastomers that have been damaged by the creation of a surface crack. The approach involves soaking the damaged elastomer for a limited time in a bath of the elastomer monomers, an ultra-violet initiator and cross-linkers to allow them all to diffuse into the specimen. The elastomer is then withdrawn from the bath at a stage where the diffusing species have only penetrated to a limited degree into the component, so that they are concentrated near its surface, including adjacent to the crack. Very soon thereafter the specimen is subjected to ultra-violet light, thereby causing the diffused species to polymerize and cross-link. As the diffusing monomers will have caused the elastomer to have swollen, the polymerization process will lock this volume expansion in place near the elastomer surface, and will have done so adjacent to the crack. Since a local expansion of the material around the crack and adjacent to its surfaces will reduce the energy release rate when the crack is forced to propagate, the swelling will have effectively toughened the elastomer against the growth of the pre-existing surface crack.